2009
DOI: 10.1525/jer.2009.4.3.99
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Biorepository Participants' Perspectives on Access to Research Results

Abstract: Disclosure of individual research results to research participants has been the subject of professional guidelines as well as scholarly commentary, yet controversy remains. To gather data on participant perspectives, we interviewed 40 individuals from the Durham, North Carolina area about a biorepository consent form and conducted an in-depth analysis of responses to a series of questions concerning access to research results. Cross-cutting themes emerged about (1) the nature of research; (2) the nature of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…14 We found that preferences regarding disclosure of individual genetic research results vary on the basis of the type of research result. Most participants in our study wanted genetic research results disclosed across all the hypothetical scenarios.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…14 We found that preferences regarding disclosure of individual genetic research results vary on the basis of the type of research result. Most participants in our study wanted genetic research results disclosed across all the hypothetical scenarios.…”
Section: Discussionmentioning
confidence: 89%
“…26,28 Only a few potential biobank participants understand these logistical barriers to disclosing research results. 14 The public believes that costs related to confirming genetic research results should be absorbed by the study budget. 15 Engaging the public in policy decisions about disclosure is important to promoting a shared responsibility for managing logistical barriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has explored the opinions of members of the general public about return of results in several different contexts, including studies focusing on predominately African American members of the general public participating in focus groups [11], members of the general public participating in focus groups [12], an online survey of the general population [13], prospective biorepository candidates [14], and diverse members of the public in focus groups [15]. These studies of the opinions of people who had not previously participated in genetic research have tended to show similar results, including a strong interest in return of results, both because of a belief that such results could help participants improve their health and due to a sense of control that is provided.…”
Section: Introductionmentioning
confidence: 99%
“…A biobanking context adds further complexity, since stored specimens and data can be used in a variety of studies that typically take place without the participant’s direct knowledge or consent (13). These studies are often conducted without any interaction with the researcher, who may be unknown to the participant.…”
Section: Informed Consent For the Collection And Storage Of Biospecimmentioning
confidence: 99%